Bibliometric and impact study of Revista Complutense de Educación (2005-2015) - Vazquez-Cano, Esteban; Belando Montoro, María Remedios; Bernal Bravo, César (Revista Complutense de Educación, 2017)
This article presents a bibliometric analysis of the Journal “Revista Complutense de Educación” in the last 10 years (2005-2015). We have analyzed 269 articles corresponding to volumes ranging from Vol. 16, N. 1 (2005) to Vol. 26, N. 3 (2015). The information was obtained from the electronic version of the journal and the following bibliometric indicators were established: number of articles according to publication year, methodology, topic, authorship index, authors’ institutional affiliation, productivity by country and citations from journals indexed in Google Scholar, Scopus, Science Citation Index, Social Science Citation Index and Arts and Humanities Citation Index. In the conclusion, we discuss those aspects that should be promoted and others which may need improvement, so that the journal may be more widely spread. Finally, the paper offers some thoughts in order to improve the journal impact and its ranking in national and international databases.